Effect of obeticholic acid on liver regeneration following portal vein embolization in an experimental model. Issue 5 (13th February 2017) - Olthof, P B; Huisman, F; Schaap, F G; van Lienden, K P; Bennink, R J; van Golen, R F; Heger, M; Verheij, J; Jansen, P L; Olde Damink, S W; van Gulik, T M
Abstract: Background: The bile salt-activated transcription factor farnesoid X receptor (FXR) is a key mediator of proliferative bile salt signalling, which is assumed to play a role in the early phase of compensatory liver growth. The aim of this study was to evaluate the effect of a potent FXR agonist (obeticholic acid, OCA) on liver growth following portal vein embolization (PVE). Methods: Rabbits were allocated to receive daily oral gavage with OCA (10 mg/kg) or vehicle (control group) starting 7 days before PVE ( n = 18 per group), and continued until 7 days after PVE. PVE of the cranial liver lobes was performed using polyvinyl alcohol particles and coils on day 0. Caudal liver volume (CLV) was analysed by CT volumetry on days –7, –1, +3 and +7. Liver function was determined by measuring mebrofenin uptake using hepatobiliary scintigraphy. Additional parameters analysed were plasma aminotransferase levels, and histological scoring of haematoxylin and eosin- and Ki-67-stained liver sections. Results: Three days after PVE of the cranial lobes, the increase in CLV was 2·2-fold greater in the OCA group than in controls (mean(s.d.) 56·1(20·3) versus 26·1(15·4) per cent respectively; P < 0·001). This increase remained greater 7 days after PVE (+1·5-fold; P = 0·020). The increase in caudal liver function at day +3 was greater in OCA-treated animals (+1·2-fold; P = 0·017). The number of Ki-67-positive hepatocytes was 1·6-fold higher in OCA-treated animals 3 days after PVE ( P = 0·045). Plasma aminotransferase levels and histology did not differ significantly between groups. Conclusion: OCA accelerated liver regeneration after PVE in a rabbit model. OCA treatment might increase the efficacy of PVE and, thereby, resectability. Surgical relevance Liver failure is the most feared complication after liver surgery, with no effective treatment options. Liver regeneration is essential to avoid liver failure, and recently bile acid signalling was implicated in the initiation of liver regeneration through the nuclear bile acid receptor farnesoid X receptor (FXR). In this study, the potent FXR agonist obeticholic acid accelerated liver regeneration following portal vein embolization in a rabbit model, in terms of liver volume, liver function and proliferation. Obeticholic acid treatment could enhance the efficacy of portal vein embolization, thereby increasing resectability, and could reduce the interval to surgery. In addition, obeticholic acid might have a place in the prevention of liver failure after liver surgery. Abstract : May enhance liver regeneration